2011
DOI: 10.1130/g31586.1
|View full text |Cite
|
Sign up to set email alerts
|

Global CO2 emission from volcanic lakes

Abstract: The global CO 2 discharge from subaerial volcanism has been estimated at ~300 Mt yr -1 . However, estimates of CO 2 emissions from volcanic lakes have not been considered. In order to improve this information, extensive research on CO 2 emissions of volcanic lakes worldwide has been performed. The observed normalized average CO 2 emission rates increase from alkaline (5.5 t km -2 d -1 ), to neutral (201.2 t km -2 d -1 ), to acid (614.2 t km -2 d -1 ) in volcanic lakes. Taking into account (1) normalized CO 2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 24 publications
4
64
2
Order By: Relevance
“…The result was 17±0.6 t d −1 for diffuse CO 2 . This value is smaller than the emission rates reported for other volcanic lakes (Pérez et al, 2011). However, in order to compare individual CO 2 emission of various volcanic lakes, it is important to consider the lake-type and the area.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…The result was 17±0.6 t d −1 for diffuse CO 2 . This value is smaller than the emission rates reported for other volcanic lakes (Pérez et al, 2011). However, in order to compare individual CO 2 emission of various volcanic lakes, it is important to consider the lake-type and the area.…”
Section: Resultscontrasting
confidence: 42%
“…During the last two decades, studies of the spatial distribution of soil CO 2 efflux has become an ideal geochemical tool for monitoring volcanic activity (Hernández et al, 2001a(Hernández et al, , b, 2006Granieri et al, 2006;Pérez et al, 2011). Several authors have demonstrated that continuous monitoring of CO 2 efflux provides important information for volcanic surveillance and seismotectonic monitoring Carapezza et al, 2004;Pérez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their aesthetic and recreational benefits (Butler, 1991;Eagles, 1997), these lakes play important economic roles such as acting as a water source for domestic use, hydroelectric power production and reservoirs for irrigation. Their global importance is also obvious: they house a remarkable variety of living organisms, making them a reservoir of biodiversity; they also participate in the global carbon cycle because they can passively and/or explosively release a large amount of CO 2 into the atmosphere (Allard et al, 1991;Freeth, 1992;Perez et al, 2011), thus participating in global climate regulation.…”
Section: Introductionmentioning
confidence: 99%
“…These surface discharges yield broad atmospheric enhancements that transport CO2 downwind (Kerrick, 2001), resulting in swaths of variably affected plants whose periods of exposure can be over hundreds of years (Cook et al, 2001). Because volcanic CO2 emissions are a vital part of the global carbon cycle (Mason et al, 2017;Schwandner et al, 2017) and have been monitored worldwide for decades (Boudoire et al 2017;Camarda et al, 2012;Perez et al, 2011;Gerlach, 1991), the rate and spatial 5 distribution of these fluxes are well-understood due to an abundance of field surveys in many volcanic systems (e.g. Hernández et al, 1998;Cardellini et al, 2003;Werner and Brantley, 2003;Giammanco et al, 2007;Lewicki et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%